2014
DOI: 10.4209/aaqr.2013.03.0082
|View full text |Cite
|
Sign up to set email alerts
|

Satellite Retrievals of Aerosol Optical Depth over a Subtropical Urban Area: The Role of Stratification and Surface Reflectance

Abstract: We explore the relationship between satellite retrievals of aerosol optical depth (AOD) and surface aerosol mass concentrations over a subtropical urban area, namely, Santiago, Chile (33.5°S, 70.6°W, 500 m.a.s.l.). We compare 11 years of AOD from the MODerate resolution Imaging Spectroradiometer (MODIS) with in situ particulate matter mass concentrations (PM). MODIS AOD reaches its maximum in summer and minimum in winter, the opposite of the annual cycle of surface PM. To improve our understanding of the relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Several other research attempts have been made to change the surface scheme in the MDT for particular urban regions and produce better AOD retrievals for those specific cities (de Almeida Castanho et al,2007Li et al, 2005;Wong et al, 2011;Zha et al, 2011;Li et al, 2012;Escribano et al, 2014;Jäkel et al, 2015). Instead of a retrieval focused on only one city, we seek a surface parameterization that is valid for cities across the globe.…”
Section: Introductionmentioning
confidence: 99%
“…Several other research attempts have been made to change the surface scheme in the MDT for particular urban regions and produce better AOD retrievals for those specific cities (de Almeida Castanho et al,2007Li et al, 2005;Wong et al, 2011;Zha et al, 2011;Li et al, 2012;Escribano et al, 2014;Jäkel et al, 2015). Instead of a retrieval focused on only one city, we seek a surface parameterization that is valid for cities across the globe.…”
Section: Introductionmentioning
confidence: 99%
“…In the near-calm regime, these authors point to the importance of submesoscale motions with length scales less than 2 km (Mahrt, 2014) which in the current site may be associated to the meandering described above. These submesoscale motions may also be related to complex aerosol layers that have been documented to appear in the Santiago boundary layer during the evening transition in the cold season (Muñoz and Alcafuz, 2012;Escribano et al, 2014). The exact nature of this phenomenon, however, has not been fully elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…For future investigations airborne imaging spectrometer measurements are suggested to characterize the slope parameters for urban areas also for different viewing geometries than the nadir observation. This will improve the corrections of the operational retrievals due to effect of the bidirectional reflectance distribution function (BRDF), since the anisotropy reflection of the surface is better described by the BRDF than assuming a Lambertian surface (Escribano et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While the resulting dark-target AOD retrieval technique shows good performance over much of the globe, the algorithm developed for dark vegetation continues to show less accurate results over surfaces with high reflectance such as arid regions (Drury et al, 2008) and urban surfaces (de Almeida Castanho et al, 2007;Oo et al, 2010;Wong et al, 2011;Zha et al, 2011;Li et al, 2012;Escribano et al, 2014). For urban surfaces in particular, de Almeida Castanho et al (2007) and Oo et al (2010) reported a positive bias of retrieved AOD over Mexico City and New York City compared to ground-based sun photometer measurements.…”
Section: Introductionmentioning
confidence: 99%